The Brand of an Athlete - Reconsidering Its Dimensions - Constantinescu, Mihaela (Journal of Emerging Trends in Marketing and Management, 2016)
In a world of multiple and diverse sports products (equipment, events, teams, athletes, merchandising, training and coaching services, broadcasting, etc.), the branding process requires a very dedicated approach in terms of product’s characteristics, customer profile and market particularities. This article presents the branding process of an athlete, considering a transition from the classical model to a more sophisticated one, in which the brand dimensions are adapted to the nowadays importance of social media and social interactions. Before presenting the results of a qualitative research on Romanian athletes’ image, the article will highlight the usefulness of measuring athlete brand image both for the athlete and the sponsor/endorser.